APPLICATION OF PHYSICAL THERAPY IN THE EARLY STAGES OF TREATMENT OF CRITICALLY ILL - Yarosh, Yu. I.; Romanyshyn М. Ya.; Fedorenko, S. M. (Rehabilitation and Recreation, 2024)
Purpose. The purpose of this study was to conduct a statistical analysis of the effectiveness of physical therapy in reducing the frequency of concomitant complications and promoting the recovery of critically ill patients undergoing treatment in the departments of anesthesiology and intensive care with the need for continuous monitoring of objective vital signs. Materials. The study used physical therapy as part of the treatment process for critically ill patients to minimize the risk of developing associated complications. Based on the methods of pedagogical observation and assessment of the amplitude of movements and the condition of the skin, the development and progression of accompanying complications in such patients was analyzed. Using these data, statistical analysis was performed using McNemar’s test. Results. According to the results of the study, a significant positive effect of physical therapy on reducing the risk of occurrence and development of concomitant complications among patients of the departments of anesthesiology and intensive care unit was established. A comparative analysis between the main and control groups of patients shows a statistically significant reduction in the number of co-complications in the group where physical therapy was applied, while in the control group no significant changes in the regression of swelling, contractures, wounds, deformities and bedsores were observed. Conclusions. The findings of the study emphasize the critical role of physical therapy in a comprehensive approach to the treatment of critically ill patients in anesthesiology and intensive care units. The results indicate a significant reduction in the occurrence of co-complications in the group of patients where physical therapy was integrated, which indicates its effectiveness in the prevention and treatment of complications in the early stages of treatment of critically ill patients in the intensive care unit.